Studies on Quality Deterioration and Metabolomic Changes in Oysters Induced by Spoilage Bacteria During Chilled Storage - Hanzheng Dou; Wenxiu Zhu; Siyang Chen; Yue Zou; Xiaodong Xia (Foods)
The correlation between spoilage bacteria and the degradation of aquatic food quality during chilled storage is substantial. However, our understanding of the precise roles of spoilage bacteria in oyster spoilage remains incomplete. The aim of this study was to explore the role of three dominant spoilage bacteria strains in oyster spoilage. Subsequently, the metabolites of spoiled oyster meat after inoculation with bacteria were analyzed using LC-MS-based untargeted metabolomics. Combining the results from various biochemical indicators of spoilage, Psychrobacter immobilis, Shewanella putrefaciens, and Photobacterium swingsii are shown to be the main spoilage bacteria in spoiled oyster meat, and their effects on changes in oyster meat quality were evaluated through total volatile basic nitrogen (TVB-N), pH, thiobarbituric acid reactive substances (TBARSs), and weight loss, respectively. The results showed that Ps. immobilis and S. putrefaciens exhibited great spoilage capacity. P swingsii, although a dominant spoilage bacterium, exhibited lower spoilage competency than the above two bacterial strains but demonstrated activity in producing microbial lipases to oxidize fats. In addition, the results of the metabolomics of spoiled oyster meat suggest that 7, 8-Dimethoxy-3-(4-methoxyphenyl)-4-oxo-4H-chromen-5-yl-2-O-pentopyranosylhexopyranoside, 1,2,3,6-Tetrahydropyridine-4-carboxylic acid, Propionic acid, and L-phenylalanine are potential markers of spoilage in oysters. These findings extend our understanding of the roles that microorganisms play in the spoilage of oysters and offer valuable insights into the development of technologies for monitoring the freshness of oysters based on these potential spoilage markers.